2020
DOI: 10.1002/cne.25068
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive map of visual projection neurons for processing ultraviolet information in the Drosophila brain

Abstract: The brain perceives visual information and controls behavior depending on its underlying neural circuits. How UV information is represented and processed in the brain remains poorly understood. In Drosophila melanogaster, UV light is detected by the R7 photoreceptor that projects exclusively into the medulla layer 6 (M 6). Herein, we imaged 28,768 single neurons and identified 238 visual projection neurons linking M 6 to the central brain. Based on morphology and connectivity, these visual projection neurons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…Central R7 and R7-DRA cells are strongly connected to different classes of MeTu cells, which form long axons terminating in spatially segregated areas of the small unit of the AOTU (Figure 10E). Previous studies proposed that different kinds of visual information may be processed by distinct parallel pathways leading towards the central brain via the AOTU (Otsuna, Shinomiya, and Ito 2014;Omoto et al 2017;Timaeus et al 2020;Tai, Chin, and Chiang 2021). Our reconstructions support this hypothesis, showing different target regions for these 2 putative MeTu types, and functional measurements confirm that the target area of MeTu-DRA cells shows polarization-sensitive responses (Hardcastle et al 2021).…”
Section: Comparison Of R7/r8 Connectivity In the Central Eye Versus The Dra Regionsupporting
confidence: 83%
See 4 more Smart Citations
“…Central R7 and R7-DRA cells are strongly connected to different classes of MeTu cells, which form long axons terminating in spatially segregated areas of the small unit of the AOTU (Figure 10E). Previous studies proposed that different kinds of visual information may be processed by distinct parallel pathways leading towards the central brain via the AOTU (Otsuna, Shinomiya, and Ito 2014;Omoto et al 2017;Timaeus et al 2020;Tai, Chin, and Chiang 2021). Our reconstructions support this hypothesis, showing different target regions for these 2 putative MeTu types, and functional measurements confirm that the target area of MeTu-DRA cells shows polarization-sensitive responses (Hardcastle et al 2021).…”
Section: Comparison Of R7/r8 Connectivity In the Central Eye Versus The Dra Regionsupporting
confidence: 83%
“…Nearly 10% of the synapses made by the central seed column R7 and R8 photoreceptors were with cells projecting directly to the central brain. Of these, the strongest targets were the MeTu cells, which resemble Tm cells, but instead of sending axons to the lobula, projected to the anterior optic tubercule (AOTU) via the anterior optic tract (Fischbach and Lyly-Hunerberg 1983;Otsuna, Shinomiya, and Ito 2014;Otsuna and Ito 2006;Omoto et al 2017;Timaeus et al 2020;Tai, Chin, and Chiang 2021;Figure 5A). Our reconstructions confirmed that MeTu cells were indeed synaptic targets of R7 (Timaeus et al 2020), and that their photoreceptor input was exclusively from R7 (Figure 5Aiv).…”
Section: Interneurons Connecting Central Eye R7 and R8 With The Central Brainmentioning
confidence: 99%
See 3 more Smart Citations